African linguistics on the prairie Selected papers from the 45th Annual Conference on African Linguistics - Kandybowicz, Jason; Major, Travis; Torrence, Harold; Duncan, Philip T. (Language Science Press, 2018)
African Linguistics on the Prairie features select revised peer-reviewed papers from the 45th Annual Conference on African Linguistics, held at the University of Kansas. The articles in this volume reflect the enormous diversity of African languages, as they focus on languages from all of the major African language phyla. The articles here also reflect the many different research perspectives that frame the work of linguists in the Association for Contemporary African Linguistics. The diversity of views presented in this volume are thus indicative of the vitality of current African linguistics research. The work presented in this volume represents both descriptive and theoretical methodologies and covers fields ranging from phonetics, phonology, morphology, typology, syntax, and semantics to sociolinguistics, discourse analysis, language acquisition, computational linguistics and beyond. This broad scope and the quality of the articles contained within holds out the promise of continued advancement in linguistic research on African languages.